2018
DOI: 10.1002/hbm.24327
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability of a stimulation‐locked evoked response to deep brain stimulation in subcallosal cingulate for treatment resistant depression

Abstract: Deep brain stimulation (DBS) to the subcallosal cingulate cortex (SCC) is an emerging therapy for treatment resistant depression. Precision targeting of specific white matter fibers is now central to the model of SCC DBS treatment efficacy. A method to confirm SCC DBS target engagement is needed to reduce procedural variance across treatment providers and to optimize DBS parameters for individual patients. We examined the reliability of a novel cortical evoked response that is time-locked to a 2 Hz DBS pulse a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 44 publications
4
23
0
Order By: Relevance
“…These results indicated that it was feasible to obtain feedback on cortical responsivity by employing a stimulation evoked potential, which can be used as a signal of optimal targeting and test–retest reliability over time. This study indicated that the p40 feature may be an activation of the forceps minor, which was consistent with previous data that linked stimulation evoked response to white matter activation (Waters et al, 2018).…”
Section: Introductionsupporting
confidence: 93%
“…These results indicated that it was feasible to obtain feedback on cortical responsivity by employing a stimulation evoked potential, which can be used as a signal of optimal targeting and test–retest reliability over time. This study indicated that the p40 feature may be an activation of the forceps minor, which was consistent with previous data that linked stimulation evoked response to white matter activation (Waters et al, 2018).…”
Section: Introductionsupporting
confidence: 93%
“…Nonetheless, indirect methods are possible. Electroencephalograms of cortical responses generated by the applied stimulus in DBS (Kibleur et al, ; Waters et al, ), and local field potentials recorded with the inactive electrodes (Smart et al, ), represent excellent opportunities for DBS biophysicists and electrophysiologists to begin to converge upon analyses that would be mutually beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, use of this implantation strategy has further allowed intraoperative and laboratory testing of behavioral and electrophysiological change with acute stimulation at the optimized target (6,(28)(29)(30). While intraoperative stimulation at the optimized target may explain the observed acute behavioral effects and postoperative improvement and carryover even in the absence of active stimulation ( Fig.…”
Section: The Development Of Current Dbs Approaches For Depressionmentioning
confidence: 99%
“…2D). One interpretation of the slow time course is that the therapeutic effects of DBS may occur in different stages with distinct mechanisms, some rapid and some slow (6,(28)(29)(30).…”
Section: Do We Have the Best Stimulation Parameters For Treatment-resmentioning
confidence: 99%